Handbook of Qualitative Research Methods in Marketing (Edward Elgar Publishing, 2006)
The Handbook of Qualitative Research Methods in Marketing offers both basic and advanced treatments intended to serve academics, students, and marketing research professionals. The 42 chapters begin with a history of qualitative methods in marketing by Sidney Levy and continue with detailed discussions of current thought and practice in: research paradigms such as grounded theory and semiotics; research contexts such as advertising and brands; data collection methods such as projectives and netnography; data analysis methods such as metaphoric and visual analyses; presentation topics such as videography and reflexivity; applications such as ZMET applied to Broadway plays and depth interviews with executives; and special issues such as multi-sited ethnography and research on sensitive topics.